Improving energy efficiency of massive MIMO using small cell network: article - Mat Zim, Alizawati (Faculty of Electrical Engineering, 2016)
Nowadays, the compaction of the cellular network resulted in increased demand in wireless data services. However, the cellular energy efficiency (EE) can be improved by densification the network topology, without bothering quality-of-service (QoS) constraint at the users. In this paper, small cell network (SCN) is applied in massive MIMO (MM) and analyze the power consumption of these two densification approaches for different QoS constraints. For this paper, three beamforming (BF) algorithms are compared which are optimal BF is using only the base station (BS), multiflow regularized zero forcing (RZF) BF and optimal spatial soft-cell coordination BF. Numerical result compared with BF algorithm proposed in different simulation parameters and show that by increasing the number of small-cell access points (SCAs), the antennas per SCAs could enhance the total system energy efficiency.